A 3.9 µm Ho3+:BaY2F8 laser directly pumped by laser diodes. Issue 20 (22nd July 2021) - Ma, Chaoqun; Zhang, Ying; Guo, Jiawei; Cai, He; Han, Juhong; Rong, Kepeng; An, Guofei; Li, Haoyu; Tan, Lijuan; Wang, You
Abstract: This study reports a mid‐infrared Ho 3+ :BaY2 F8 laser directly pumped by laser diodes (LDs). A finite element method (FEM) was used to calculate the temperature and thermal stress distributions inside the Ho 3+ :BYF crystal. The damage conditions have been evaluated on the basis of the experimental results. Using 889 nm LDs with the repetition frequency and pulse duration of 13 Hz and 100 μs, respectively, an output pulse energy of 1.05 mJ at 3.9 μm for the pump pulse energy of 336.8 mJ was achieved. The study might be useful for constructing a compact and robust mid‐infrared laser.